N-Heterocyclic carbene catalyzed regioselective oxo-acyloxylation of alkenes with aromatic aldehydes: a high yield synthesis of alpha-acyloxy ketones and esters - Reddi, Rambabu N.; Malekar, Pushpa V.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
An N-heterocyclic carbene (NHC)-catalyzed reaction of alkenes with aromatic aldehydes providing for a high yield synthesis of alpha-acyloxy ketones and esters has been described. This unprecedented regioselective oxidative process employs NBS and Et3N in stoichiometric amounts and O-2 (1 atm) as an oxidant under ambient conditions in DMSO as a solvent.